The Influence of Regulation Implementation on The Intensity of Discipline for Sixth Grade of Kulliyatul Muallimin Islamiyah at Darussalam Gontor Modern Islamic Institution - Noor Syahid; Muti’ah Nur Hikmah (At-Ta'dib, 2019)
Islamic Education shapes people's behavior and work in accordance with the law of God. Darussalam Gontor Islamic Institution for Girls Campus 3 is an educational institution that forms its students in order to obey the law of God and the good morals with strong discipline. When the students comply with the order of boarding, indirectly it will improve discipline and students character. Therefore, the researcher intends to conduct a review of the effect of the implementation regulation of boarding to the Intensity of Discipline for Sixth Grade of Kulliyatul Muallimin Islamiyah at Darussalam Gontor Modern Islamic Institution. This research method used is Quantitative Research Courses Associative Causal. The population in this research is 479 students. Determine the sample, the researcher used the method of Suharsimi Arikunto with an error rate of 25%, therefore researchers took 120 students to become the sample with Stratified Random Sampling Method. For data collection, the researchers used questionnaires and documentation. With the results of implementation of the order of the 6th grade of KMI reached an average of 92.28 with high quality, intensity disciplinary of the 6th grade KMI reached an average of 166.64 with high quality, and their influence on the intensity of the order of boarding school discipline of 6 KMI with the presentation of the results of R Square 0.423 with respect to the average value of the R Square that found there are significantly.